Study of Ultrasound-Assisted Low-Pressure Closed Acid Digestion Method for Trace Element Determination in Rock Samples by Inductively Coupled Plasma Mass Spectrometry - Xijuan Tan; Yunxiu Ren; Ting Liang; Denghong Wang (Molecules)
In this paper, a method of ultrasound-assisted low-pressure closed acid digestion followed by inductively coupled plasma mass spectrometry (ICP-MS) analysis was proposed for trace element quantification in rock samples. By using 1.5 mL of a binary acid mixture of HNO3–HF with a ratio of 2:1, rock powder samples of 50 mg were completely decomposed in 12 h at 140 °C after 4 h of ultrasonic treatment with or without pressure relief procedure. The element extraction efficiency of this method was evaluated via the yielded relative errors (REs) of the trace elements in a series of geological standard reference materials (SRMs) with compositions from basic to acidic. It was found that the contents of trace elements (i.e., 36 metal elements from Li to U) in basalt BCR-2, diabase W-2a, andesite AGV-2, granodiorite GSP-2, and granite GSR-1 were comparable with the reported reference values, giving REs with absolute values less than 10%. It was also found that clear solutions without sample powder residues by naked-eye observation can be obtained when using the low-pressure closed decomposition method without ultrasonic pretreatment. The quantification results, however, were found to be negatively biased for most of the studied trace elements, and, in particular, the content bias of Zr in SRM GSP-2 was down to −86.28% due to the low extraction efficiency of refractory minerals of the low-pressure closed digestion method. By applying this proposed digestion strategy, the decomposition property of the ternary combination of HNO3–HF–mannitol in terms of trace element quantification accuracy was also investigated. Results showed that the concentrations of trace elements in the studied SRMs were consistent with the reference values, giving REs within ±6.94%, which revealed that there was no deterioration of extraction efficiencies of trace elements and neglected mass interferences from mannitol. This study demonstrated the essential role of ultrasound irradiation in rock sample decomposition to achieve the high extraction efficiency of trace elements under a low-pressure environment, and the developed approach with promising future applications in geoscience exhibited considerable merits, including a high extraction efficiency, feasible digestion process, less time consumption, and lower safety associated risks.